Political Reflection of Environmental Law Towards Regional Autonomy Law Products Holistic - Ecological Perspective - Binov Handitya; Wafda Vivid Izziyana (Jurnal Justiciabelen, 2023)
The principle of implementing a broad and intact regional autonomy that is placed on districts and cities, then Environmental Affairs are affirmed as government affairs that must be implemented by districts and cities. From the above provisions there are three important findings related to environmental management policies. First, that the region has been given the right to manage the autonomy of Natural Resources in the region, both on land and in the sea. Second, to exercise the right to regulate and take care of their own local household affairs over these natural resources, various legal products can be issued as long as they do not conflict with higher legislation or public interests. Third, the right of management of natural resources given to the region as well as followed by the responsibility of the region to preserve the environment in accordance with legislation. This research method is juridical normative. This study was conducted by examining library materials, ranging from primary legal materials, secondary legal materials and tertiary legal materials. the results of the study explain a holistic-ecological regional autonomy law product requires some fundamental changes. First, the format of granting autonomy to regions must be clear and detailed without excluding the diversity, characteristics, and capabilities of each region. Second, the scope of authority is not only "control", but includes aspects from planning to law enforcement. Third, the laws and regulations above the regional regulation must also be clear, synchronous and harmonious between certain legal regimes and regional autonomy legal regimes, such as between environmental law, tax law (PDRD), and regional autonomy law. Fourth, policy integration in the preparation of local regulations also requires a planning legal instrument in the form of regional legislation programs (prolegda), through Prolegda that is really compiled comprehensively (not just a list of priorities Raperda without clear justification). Fifth, associated with the theory of environmental sovereignty (ecocracy), the regional autonomy policy as the implementation of the concept of democracy should not ignore the interests of Environmental Protection. The welfare to be achieved through regional autonomy policies must synergize the principles of ecological sustainability. The six academic manuscripts are the results of research or legal studies and other research results on a particular problem that can be scientifically accounted for regarding the regulation of the problem in a form of Bill or draft law